Epidemiological profile of patients suffered by a stroke and its associated factors in the municipality of Piancó/PB - Tomé, Anna Beatriz Silva; Sá, Aralinda Nogueira Pinto de; Queiróz, Bernardo Andrade de; Pereira, Daniel Galdino de Araújo; Vilhena, Elysa Stephannya Dobrões; Abrantes, Ester Emanuele; França, Juliana de Araújo; Almeida, Luana Barreto de; Oliveira, Marianna Adijuto de; Paiva, Marina Farias; Ribeiro, Natália Queiroz Silva (JRG Journal of Academic Studies, 2024)
A Stroke quickly and unexpectedly interrupts the blood flow to a region of the brain, causing symptoms such as paralysis and many limitations, which harm the quality life of the individuals. Various studies point to the occurrence of strokes in Paraíba and the need for preventive actions, care and monitoring, trying to minimize the damage caused by these complications. This research is a documentary study, which aims to identify the epidemiological profile of patients affected by stroke and its associated factors in the municipality of Piancó/PB, through secondary data collection. The search was carried out by obtaining data from the Municipal Health Department of Piancó/PB, in addition to information relating to the individual's pathology collected in the information system, TABWIN – DATASUS, and variables relating to sex, education, age and income were extracted from the Prontuário Eletrônico do Cidadão (PEC). The results showed important data that reflect the reality of the locality, and made it possible to draw an epidemiological profile of patients who had a stroke in Piancó. In a total of 53 cases of stroke between 2018 and 2021, 28 were male (52.8%) aged between 54 and 93 years and 25 were female (47.2%) aged between 55 to 100 years. Of this total, 71.7% were not literate. The average monthly income of individuals was 1.11 minimum wages. It is noteworthy that only nine patients did not present risk factors for stroke, while 44 had risk conditions, including systemic arterial hypertension, diabetes mellitus, obesity and smoking. Thus, studies like these reveal important findings for the academic and social environment, providing information for future research on the subject.